Ai-Driven Robotics and Automation: The Evolution of Human-Machine Collaboration - Shahrukh Khan Lodhi; Shah Zeb (Journal of World Science, 2025)
AI-driven robotics has transformed industries through enhanced automation, yet challenges like ethical dilemmas, workforce displacement, and cybersecurity gaps persist. While prior research focused on functional applications, emotional intelligence and bio-inspired designs remain underexplored. This study examines the integration of emotionally intelligent and bio-inspired robots into human-machine collaboration, evaluates ethical governance frameworks, and proposes solutions for global regulatory harmonization. A mixed-method approach was employed, combining systematic literature reviews of 72 peer-reviewed articles (2014–2024) and case studies of AI robotics in healthcare, manufacturing, and agriculture. Data were analyzed via thematic coding and SWOT analysis. Key innovations include socially intelligent robots for elderly care, BCIs for neural-controlled prosthetics, and swarm robotics for precision agriculture. Ethical challenges like bias in hiring algorithms and accountability gaps in autonomous systems were identified, necessitating transparent AI audits. The research advocates for adaptive regulatory models to balance innovation with ethical safeguards, emphasizing human-centric collaboration. It calls for international standards to address bias, cybersecurity, and liability, offering a roadmap for policymakers and industries to harness AI robotics responsibly.